Synergistic Toughening Effect of Nucleating Agent and Annealing Treatment and Morphological Research on Block Copolymerization Polypropylene. Issue 3 (11th February 2019) - Li, Caili; Zhang, Yake; Leng, Jinhua; He, Bobing; Chen, Xian
ABSTRACT: The toughening effects of α and β nucleating agents (α-NA and β-NA) and annealing treatment on block copolymerization polypropylene (PPB) were ascertained. The synergistic effect of β-NA and the annealing treatment at 130°C for 3 h impacted the toughness greatly for all test temperatures (−15, 0 and 23°C), specifically, the notched Izod impact strength tested at −15°C increased from 7.3 kJ/m 2 to 30.1 kJ/m 2 . Moreover, the addition of α-NA or the annealing treatment also improved the toughness of PPB. The changes of the crystallite morphology and multiphase structure play an important role on the toughening. GRAPHICAL ABSTRACT: